Pengaruh Burnout terhadap Turnover Intention dengan Quality of Work Life sebagai Mediasi - Daniela, Stefanie; Alberd (Jurnal Informatika Ekonomi Bisnis, 2025)
The progress of urbanization and modernization in the industrial sector has brought major changes to the position and role of women in society. Many women workers who are already families experience the dual pressure between the demands of work and household responsibilities. This phenomenon illustrates the changing dynamics of the family economy, where the role of women is increasingly dominant as the main breadwinner, often even the only source of family income. In this study, we explored the effect of burnout on turnover intention in female workers who have families in Pontianak, mediated by Quality of Work Life. The focus of the research is directed to find out the extent to which the level of physical, emotional, and mental fatigue (burnout) can drive the intention to change jobs, as well as the role of work life quality in weakening or strengthening these relationships. The method used in this study is a quantitative method, which aims to measure the relationship between variables objectively, systematically, and statistically analyzed. The population is female workers who have families in Pontianak. Sampling was determined using the purposive sampling method. Data collection was carried out by distributing questionnaires compiled based on the indicators of each research variable. There were 124 respondents which were then processed using WarpPLS 7.0. The results of the study show that burnout has a positive and significant influence on turnover intention. The findings of this study also show that QWL is a significant mediator in the relationship between burnout and turnover intention.